The historical overview of the choral singing in Kosovo - Rasimi, Adhurim (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
This research presents the historical development of Choral Singing in Kosovo within the context of general cultural and educational development at various historic times to present days. It mentions chronologically the choral groups that have been involved in the progress of amateur choral singing, especially at the beginning of this cultural activity. The first composers who contributed to the development of this musical genre are also pointed out. In this paper, we talk about the choral singing in general education (in primary and secondary schools), proceeding with choral singing in the context of music education (in primary and secondary schools of music). In addition, it provides the reader with the insight about the contribution of most significant educational and cultural institutions that participated in the professional development of choral singing such as: Faculty of Music, Choir „Collegium Cantorum“, Choir of RTP (Radio and Television of Prishtina), Kosovo Philharmonic Choir, etc. It also deals with the cultural situation in the 1990s as a result of the difficult time that Kosovo had in this period. In addition, it deals with the development of choral singing after the 1999s, i.e. after the war when Kosovo was under the international protectorate till its independence in 2008; then it proceeds with the development of choral singing to the present day.